Analysis of Deformation Characteristics of Expansive Soil Embankment under Extreme Atmospheric Action. Issue 3 (September 2019) - Xiongwei, Li; Baochun, Zhou; Liang, He; Jianqun, Zhu
Abstract: By setting extreme boundary conditions, the working behaviour of expansive soil embankment under atmospheric action is analyzed. The embankment is subjected to continuous rainstorm for 6 days after 3 months evaporation under hot weather. On the basis of fracture description, the deformation process considering infiltration is calculated. The deformation of embankment treated with lime-soil and without lime-soil is compared, and the influence of different water levels is taken into account. The results show that expansive soil embankment will produce large deformation in evaporation and rainfall environment. When expansive soil embankment is treated with lime-soil enclosure, the deformation becomes small. This treating method can effectively reduce the influence of extreme environment, and ensure the deformation of embankment stably.